Biodegradation of polybrominated diphenyl ethers and strategies for acceleration: A review. (April 2018) - Zhao, Chenghao; Yan, Ming; Zhong, Hua; Liu, Zhifeng; Shi, Liangsheng; Chen, Ming; Zeng, Guangming; Song, Biao; Shao, Binbin; Feng, Haopeng
Abstract: Polybrominated diphenyl ethers (PBDEs), a class of brominated flame retardants (BFRs), are widely used in various commercial products. PBDEs have attracted increasing attention due to their toxicity and bioaccumulation potential. Biodegradation associated technologies are cost-effective and environmentally friendly for possible removal of PBDEs from the environments. In this review, both aerobic and anaerobic biodegradation of PBDEs and the methods for accelerated degradation are discussed. Generally, the degradation of higher PBDEs (higher degree of bromination) is slower than that of lower PBDEs (lower degree of bromination) under both anaerobic and aerobic conditions. The aerobic degradation pathways of PBDEs include cleavage of aromatic ring, debromination, and hydroxylation, while reductive debromination dominates the initial pathway of anaerobic degradation. A number of methods to overcome the chemical inactivity and low bioavailability of PBDEs for degradation enhancement are discussed, such as the addition of external carbon sources, surfactants and vitamin B12 . In addition, coupling of chemical degradation and biodegradation is also reviewed. Graphical abstract: Polybrominated diphenyl ethers (PBDEs) biodegradation and enhancement methods.Image 1 Highlights: Biodegradation and enhancement methods for PBDEs were introduced. PBDEs biodegradation was related to the degree and location of bromines. Multiple methods were the appropriate ways for PBDEs bioremediation. Insights and prospects on PBDEs biodegradation were proposed.